The Implementation Of Policy In The Restructuring Of Financing In Islamic Banks In The Province Of Aceh, Indonesia - Muksal, Muksal; Ayumiati, Ayumiati; Humaira, Annisa (Program Studi Perbankan Syariah FEBI UIN Ar-Raniry, 2024)
The objective of this study is to investigate the internal policies pertaining to the reconstruction funding of Bank Syariah Indonesia (BSI) in Aceh Province. An examination of qualitative research methodologies through the medium of an interview. The research findings indicate that the bank BSI has effectively executed its policies, which have been deemed favorable. This initiative has significantly alleviated the challenges faced by consumers, particularly Micro, Small, and Medium Enterprises (MSMEs) impacted by the Covid-19 pandemic. It has provided necessary financial support to enable their survival and sustainability beyond the crisis. There are no significant hurdles encountered subsequent to the reconstruction undertaken by the party bank, owing to the implementation of its policies. The implementation of Sharia law has significantly contributed to the improvement of customer financing in the province of Aceh.